2015
DOI: 10.1590/s0100-204x2015001200011
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade e potencial nutracêutico do leite bovino em diferentes sistemas de produção e estações do ano

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da interação entre sistemas produtivos e estações do ano sobre a qualidade química e microbiológica do leite bovino, além de propor um índice de potencial nutracêutico do perfil de ácidos graxos do leite. Três propriedades foram avaliadas mensalmente, durante as diferentes estações do ano, em quatro graus de especialização dos sistemas de produção: altamente especializado, especializado, semiespecializado e não especializado. Os sistemas de produção e as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
3
0
5
Order By: Relevance
“…With the exception of casein, all the constituents of milk had lower values in the dry season (seasons 3 and 4). Gonzalez et al (2004), Simioni et al (2014) and Vargas et al (2015) also found variation in bovine milk composition according to the months of the year, and pointed out low quantitative and qualitative supply of forage as the probable cause that occurs at some periods of the year. The reduction in levels of fat, protein and total solids, which are substantially influenced by nutritional management (ROSA et al, 2012), reaffirm this effect.…”
Section: Resultsmentioning
confidence: 97%
“…With the exception of casein, all the constituents of milk had lower values in the dry season (seasons 3 and 4). Gonzalez et al (2004), Simioni et al (2014) and Vargas et al (2015) also found variation in bovine milk composition according to the months of the year, and pointed out low quantitative and qualitative supply of forage as the probable cause that occurs at some periods of the year. The reduction in levels of fat, protein and total solids, which are substantially influenced by nutritional management (ROSA et al, 2012), reaffirm this effect.…”
Section: Resultsmentioning
confidence: 97%
“…Nesse sentido, os maiores valores de CCS encontrados no verão podem ser resultantes das altas temperaturas dessa estação na região Sul do Brasil, o que poderia resultar em estresse térmico e limitação da resposta imunológica dos animais a doenças e sua susceptibilidade à invasão do úbere por microrganismos, resultando em aumento na CCS do leite (5) .…”
Section: Discussionunclassified
“…Sistemas de produção e estações do ano interferem na qualidade físico-química e microbiológica do leite (5) , porém existem poucas informações referentes ao efeito conjunto desses fatores na qualidade dessa matéria-prima.…”
Section: Introductionunclassified
“…Due to this fact, there may have been small variations in lactose concentration in the milk % TDN in the diet for dairy goats of the supplemented animals, thus explaining the slight but significant difference (p<0.05) in the milk from goats supplemented with concentrate compared with the milk from goats of the control group, without concentrate (Table 4) (Gonzáles et al, 2004;Abrantes et al, 2015). Vargas et al (2015) reported that the season may enhance the stress condition of the animals, either by reducing dry matter intake so that the animals cannot reach their daily needs, mainly in energy, or because of the hormonal mechanisms triggered by the stress causing weak immune response to the microorganisms, making them susceptible to diseases, such as mastitis that can also affect the quality and physical and chemical parameters of milk.…”
Section: Discussionmentioning
confidence: 99%